2023
DOI: 10.1109/access.2023.3239303
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing and Siting of PV and Battery Based Space Microgrids Near the Moon’s Shackleton Crater

Abstract: Space mission cost and feasibility depend mainly on the size and mass of the payload. This paper investigates the optimal photovoltaic (PV) array and battery size and mass for an islanded PV-battery powered space microgrid (MG) at the lunar south pole. The PV arrays are considered to be installed on top of towers to increase solar energy harvesting. Considering the dependency of the generated power from PV arrays on the tower height, different tower heights of 10, 50, and 100 m are investigated. The paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(86 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In this paper, the available power of PV arrays made up of multi-junction (MJ) GaInP/GaAs/Ge PV cells based on III-V semiconductor technology is estimated using the methodology first proposed in [7] and later updated by the authors in [13] as shown in Fig. 2.…”
Section: A Estimating Pv Power Generationmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, the available power of PV arrays made up of multi-junction (MJ) GaInP/GaAs/Ge PV cells based on III-V semiconductor technology is estimated using the methodology first proposed in [7] and later updated by the authors in [13] as shown in Fig. 2.…”
Section: A Estimating Pv Power Generationmentioning
confidence: 99%
“…It is worth noticing that the degradation of PV cells due to the particle radiations and low lunar temperatures is not considered in this study. A detailed description of determining the PV power generation profile from the illumination time-series profile is discussed in [13].…”
Section: A Estimating Pv Power Generationmentioning
confidence: 99%
See 3 more Smart Citations